Strategi Manajerial dalam Meningkatkan Literasi dan Kepemimpinan Siswa Melalui Program Budaya Positif Gerakan Literasi Bahasa - Maryam, Maryam; Jasman, Oktapia; Febrianti, Farida (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This article focuses on efforts to enhance student leadership by cultivating a literacy culture at SMKS PGRI Enrekang. The background for this initiative stems from the low literacy skills of students, as revealed in the Education Quality Report based on the National Assessment. The aim of this community service program is to foster student leadership through the implementation of the Positive Culture Language Literacy Movement (BUSITI GELISA). The method employed in this program is participatory and collaborative, engaging students in various literacy activities such as book clubs, creative writing, peer mentoring, and the selection of literacy ambassadors. The results of the implementation show a significant increase in students' literacy skills, self-confidence, and initiative. The BUSITI GELISA program has proven to be an effective model for integrating literacy habits with the development of leadership qualities in schools.